Synergistic Efficacy of Doxycycline and Florfenicol Against Aeromonas hydrophilia and Morganella morganii Infections in Pelodiscus sinensis with Skin Ulcer Disease - Ziwen Cai; Wenjing Zhang; Yun Wang; Zhaoying Yang; Xiaolei Lei; Xiaomin Shi; Mengze Du; Xiaoye Liu (Veterinary Sciences, 2025)
The intensive farming of Pelodiscus sinensis (P. sinensis) for its medicinal and economic value has led to an increased incidence of bacterial skin infections, commonly treated with antibiotics. However, rising antibiotic resistance has reduced the effectiveness of these treatments, highlighting an urgent need for alternative therapeutic approaches. In this study, we isolated and identified pathogenic bacteria (Aeromonas and Morganella) from P. sinensis affected by skin ulcer disease at a turtle farm in Beijing. Antibiotic resistance was evaluated using the checkerboard microdilution method and the in vitro antibacterial efficacy of a florfenicol–doxycycline combination therapy was assessed. A total of 30 bacterial isolates were obtained, primarily Morganella and Aeromonas species. Among these, 83.3% of Morganella and 57.14% of Aeromonas isolates demonstrated multidrug-resistance. The florfenicol–doxycycline combination yielded lower fractional inhibitory concentration (FIC) values, indicating synergistic or additive effects. Animal experiments have shown that florfenicol in combination with doxycycline can achieve better therapeutic effects with less drug. These findings support that combination antibiotic therapies help in managing skin ulcer disease in P. sinensis and offer valuable insights for clinical applications.